Reverse Privatization as a Reaction to the Competitive Environment: Evidence from Solid Waste Collection in Germany - Juri Demuth; Hans W. Friederiszick; Steffen Reinhold (Review of Industrial Organization, 2021)
After earlier waves of privatization, local governments have increasingly taken back control of local service provisions in some sectors and countries and instead started providing those services themselves (reverse privatization). Using a unique panel dataset on the mode of service provision for solid waste collection for German municipalities that cover the years 2003, 2009, and 2015, we investigate the motives for reverse privatization. Our results show that—in deciding whether to insource or not—municipalities react to the cost advantages of private suppliers as well as to the competitive environment and municipal activity: there is more switching to insourcing in concentrated markets and in markets with horizontally or vertically related public services. Local interest groups influence this decision as well.
Keywords: 330; Reverse privatization; Solid waste collection; Mixed oligopoly; State-owned enterprises; Competition law enforcement; Logit regression